Gendered labor market responses to increased import competition - Leoni Alewell; Pia Heckl (CESifo GmbH, 2025)
Over the last decades, globalization has led to more integrated markets which fostered the transformation of economies around the world. How do domestic labor markets react to increased competition from abroad? This Policy Brief examines the effect of an import shock on the Mexican labor market focusing particularly on gender differences.
Keywords: 330; Internationaler Wettbewerb; Import; Chinesisch; Arbeitsmarkt; Geschlecht; Schwarzarbeit; Mexiko